A Study of Cho-Kwon-Srivastava Operator with Applications to Generalized Hypergeometric Functions. (9th July 2014) - Ghanim, F.; Darus, M.
Abstract : We introduce a new class of meromorphically analytic functions, which is defined by means of a Hadamard product (or convolution) involving some suitably normalized meromorphically functions related to Cho-Kwon-Srivastava operator. A characterization property giving the coefficient bounds is obtained for this class of functions. The other related properties, which are investigated in this paper, include distortion and the radii of starlikeness and convexity. We also consider several applications of our main results to generalized hypergeometric functions.